COVID-19 STRESS IN USERS GADGETS AND COVERAGE COVID-19 VACCINATION - Maria Megaloma H Gaharpung; Yenita Lusia Welin; Debi Angelina Brother Barus; Hendrikus Pedro (Jurnal Scientia, 2023)
COVID-19 vaccination is one of the immunization media provided government as one method For guard health body human , besides that too for combat or minimize COVID-19 disease . Information about vaccination can obtained through gadgets. Study This aim For know COVID-19 stress on Gadget Users and Abilities COVID-19 vaccination . Data collection was carried out with method survey quantitative with approach comparative and use adaptation of the COVID Stress Scales from Taylor et al, (2020). A total of 338 responses fill in online scale . Data analysis using ANOVA technique for see difference stress between respondents who have not get vaccination , respondents who have get vaccination dose I and respondents who have get vaccination dose II. The results of the data analysis show that there is difference level stress (F: 6.143, P: 0.002) for respondents who have not vaccinated , respondent with vaccination dose I and the respondent with vaccination dose II. Respondents vaccination dose II has level more stress high (Mean = 167.36) compared with respondent vaccination dose I (Mean = 152.63) and respondents who did not vaccinated (Mean = 147.37). The stress of COVID-19 drives respondent For look for vaccination For protect self from exposure to COVID-19.